The role of tailored biochar in increasing plant growth, and reducing bioavailability, phytotoxicity, and uptake of heavy metals in contaminated soil - Mohamed, Badr A.; Ellis, Naoko; Kim, Chang Soo; Bi, Xiaotao (Pergamon Press Ltd., 2017)
Microwave-assisted catalytic pyrolysis was investigated using K3PO4 and clinoptilolite to enhance biochar sorption affinity for heavy metals. The performance of resulting biochar samples was characterized through their effects on plant growth, bioavailability, phytotoxicity, and uptake of heavy metals in a sandy soil contaminated with Pb, Ni, and Co. The produced biochars have high cation-exchange capacity (CEC) and surface area, and rich in plant nutrients, which not only reduced heavy metals (Pb, Ni, and Co), bioavailability and phytotoxicity, but also increased plant growth rate by up to 145%. The effectiveness of biochar in terms of reduced phytotoxicity and plant uptake of heavy metals was further improved by mixing K3PO4 and clinoptilolite with biomass through microwave pyrolysis. This may be due to the predominance of different mechanisms as 10KP/10Clino biochar has the highest micropore surface area (405 m(2)/g), high concentrations of K (206 g/kg), Ca (26.5 g/kg), Mg (6.2 g/kg) and Fe (11.9 g/kg) for ion exchange and high phosphorus content (79.8 g/kg) for forming insoluble compounds with heavy metals. The largest wheat shoot length (143 mm) and lowest extracted amounts of Pb (107 mg/kg), Ni (2.4 mg/kg) and Co (63.9 mg/kg) were also obtained by using 10KP/10Clino biochar at 2 wt% load; while the smallest shoot length (68 mm) and highest extracted amounts of heavy metals (Pb 408 mg/kg, Ni 15 mg/kg and Co 148 mg/kg) for the samples treated with biochars were observed for soils mixed with 1 wt% 10Clino biochar. Strong negative correlations were also observed between biochar micropore surface area, CEC and the extracted amounts of heavy metals. Microwave-assisted catalytic pyrolysis of biomass has a great potential for producing biochar with high sorption affinity for heavy metals and rich nutrient contents using properly selected catalysts/additives that can increase microwave heating rate and improve biochar and bio-oil properties. (C) 2017 Elsevier Ltd. All rights reserved.